Does accelerated patenting information dissemination affect managers' (un)ethical behavior?: evidence from the American Inventor's Protection Act and crash risk - John, Kose (Journal of business ethics, 2025)
Motivated by the ethical dilemma in managerial financial reporting decisions, we explore and reveal an unintended "crash" consequence following accelerated patenting information dissemination. Employing the American Inventor’s Protection Act (AIPA) that accelerated the publication of patent applications, we find that accelerated dissemination of patenting information increases stock price crash risk. This effect is stronger when treated firms are technologically closer to their rival firms and more concerned about proprietary costs. Further analyses indicate that, the heightened crash risk following the AIPA is attributable to managers shifting towards less timely bad news disclosures. Overall, our study documents that accelerated dissemination of patenting information induces managers to strategically withhold negative information, which adds to the comprehension of what and how (un)ethical decisions are undertaken by managers.